2018
DOI: 10.1371/journal.pone.0203676
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in health and mental health in France. The results of a 2010 population-based survey in Paris Metropolitan Area

Abstract: The present study aimed to assess socioeconomic inequalities in general and mental health, depression and substance use disorders (daily tobacco use, hazardous alcohol use). Data from the 2010 SIRS (French acronym for Health, Inequalities, and Social Ruptures) study, which is deemed to be representative of the French-speaking adult population living in the Paris Metropolitan Area, were analysed. Different socioeconomic position indicators were selected: education, income and perceived financial status. Absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
10
15
0
1
Order By: Relevance
“…The higher prevalence of both MDE and AUD among those in the lowest SES group could lend support to this nding. This is consistent with other studies which showed that people who have a low SES and are experiencing a greater social disadvantage generally suffer poor health outcomes, including depressive and substance use disorders, have more disabilities, and poorer access to health care [9,10,17,19,38,41,42]. Whether the strong association between depressive episode and harmful-dependent drinking in the high and low SES groups is driven by a high accessibility to alcohol in the high SES group or an enhanced susceptibility to negative health outcomes when exposed to chronic di culties among the low SES group is plausible and deserves further research to elucidate mechanisms explaining this social disparity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The higher prevalence of both MDE and AUD among those in the lowest SES group could lend support to this nding. This is consistent with other studies which showed that people who have a low SES and are experiencing a greater social disadvantage generally suffer poor health outcomes, including depressive and substance use disorders, have more disabilities, and poorer access to health care [9,10,17,19,38,41,42]. Whether the strong association between depressive episode and harmful-dependent drinking in the high and low SES groups is driven by a high accessibility to alcohol in the high SES group or an enhanced susceptibility to negative health outcomes when exposed to chronic di culties among the low SES group is plausible and deserves further research to elucidate mechanisms explaining this social disparity.…”
Section: Discussionsupporting
confidence: 91%
“…We also found a signi cant association of MDE with either hazardous or harmful-dependent drinking in those with a secondary school or higher level of education but not in those with a primary school level of education, and a higher AOR among those living in urban areas compared to those living in rural areas. Inequalities in the prevalence of MDE and AUD between levels of wealth index, education, employment, and area of residence were also found, which supports studies investigating social inequalities in mental health conditions within a country [11,13,19,38].…”
Section: Discussionsupporting
confidence: 78%
“…The higher prevalence of both MDE and AUD among those in the lowest SES group could lend support to this nding. This is consistent with other studies which showed that people who have a low SES and experiencing greater social disadvantage generally suffer poor health outcomes, including depressive and substance use disorders, have more disabilities, and poorer access to health care [8,10,11,15,34,38,39]. On the other hand, people in the highest SES group may have more means to access alcohol or other drugs for selfmedication when they get depressed.…”
Section: Discussionsupporting
confidence: 91%
“…We also found a signi cant association of MDE with harmful-dependent drinking in those with a secondary school or higher level of education but not in those with a primary school level of education, and a higher AOR among those living in urban areas compared to those living in rural areas. Inequalities in the prevalence of MDE and AUD between levels of wealth index, education, employment, and area of residence were also found, which supports studies investigating social inequalities in mental health conditions within a country [8,19,34,35].…”
Section: Discussionsupporting
confidence: 79%
“…Inequalities in the prevalence of AUD and MDE between levels of wealth index, education, employment and urban vs. rural populations were also found, which supports studies investigating social inequalities in mental health conditions within a country [28,7,15,29].…”
Section: Discussion Main Findings Interpretations and Comparisons Wisupporting
confidence: 79%